Depression in medical students: reviewing its prevalence, risk factors, consequences, and management in order to provide student treatment recommendations for the Polish medical education system - Wallace, Brian E.; Masiak, Jolanta; Pabis, Matthew R. (Polish Journal of Public Health, 2013)
The information regarding the state of mental health among medical students, particularly regarding depression, is a significant cause for concern. In fact, current research shows that approximately twenty five percent of medical students in the United States exhibit symptoms of a mental health disorder and some reports suggest that the rate of depression among medical students is more than twice that of the general population. Furthermore, the rate of depression has been noted to increase throughout the course of medical school although some reports suggest that the transition years from basic-to-clinical sciences yield the highest prevalence numbers. Nonetheless, the ever-increasing academic demands of medical school can create significant stress for these students who often experience subjective anxiety, which co-occurs depression, and may ultimately influence their overall health and wellbeing.However, medical students commonly underestimate the risk of depression associated with their population and although they are taught to view mental health disorders in a manner similar to any other disease, depressed students tend to associate a certain stigma with depression when coping with their own mental health issues. As a result, medical students with depression often remain undiagnosed and undertreated despite the availability of effective medications and confidential mental health services. The increased prevalence of depression and its under-diagnosis in this population may have negative consequences that extend beyond the individual student. This paper examines the prevalence of depression among medical students, possible reasons and consequences of their limited treatment, and solutions that have been proposed to help alleviate this burden. Particular emphasis is placed on the latter in order to provide recommendations for depressed medical student counseling and treatment options within the Polish medical education system.